Telling lives in India : biography, autobiography, and life history - Arnold,David(Editor) Blackburn,Stuart(Editor) (Indiana University Press, 2004)
Essays drawn from a "Life Histories" project established at the School of Oriental and African Studies ... in London and presented at a workshop held on 15-17 May 2000, British Library, London.